2014
DOI: 10.1521/aeap.2014.26.5.398
|View full text |Cite
|
Sign up to set email alerts
|

The IMEA Project: An Intervention Based on Microfinance, Entrepreneurship, and Adherence to Treatment for Women With HIV/AIDS Living in Poverty

Abstract: A number of issues affect adherence to treatment and quality of life among women living with HIV/AIDS. In particular, women living in poverty have a higher risk of mortality due to their vulnerable conditions and socioeconomic exclusion. The objective of this study was to evaluate the effectiveness of an intervention that combines microfinance, entrepreneurship and adherence to treatment (IMEA) for women with HIV/AIDS and living in poverty in Cali, Colombia. A pre-post research design without a control was uti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Our findings contribute to the scientific literature examining the efficacy of economic interventions in improving HIV treatment adherence [18, 2427], and expand this evidence base to an adolescent population. To our knowledge, this is the first study to utilize a randomized experimental design to assess the longitudinal effects of an economic intervention on HIV viral suppression among adolescents.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Our findings contribute to the scientific literature examining the efficacy of economic interventions in improving HIV treatment adherence [18, 2427], and expand this evidence base to an adolescent population. To our knowledge, this is the first study to utilize a randomized experimental design to assess the longitudinal effects of an economic intervention on HIV viral suppression among adolescents.…”
Section: Discussionmentioning
confidence: 52%
“…The published literature has largely focused on poor adults who are living with HIV and includes strategies relating to financial and economic incentives [18, 24], food assistance [18, 25], medication vouchers and subsidies [26, 27], as well as microfinance [26] and entrepreneurial education [27]. By and large, these studies have found significant improvements in treatment adherence among HIV-infected adults.…”
Section: Introductionmentioning
confidence: 99%
“…The preceding feasibility study was not powered to detect significant differences in CD4 counts but found positive trends (Pandit et al, 2010). Two studies that combined ART adherence support and HES, including microcredit, yielded positive findings in relation to self-reported adherence (Arrivillaga et al, 2014), Support with access to school was not a significant predictor of ART adherence.…”
Section: Promotion Interventionsmentioning
confidence: 93%
“…interventions aimed at supporting ART adherence. One, conducted with females in Colombia, found that self-reported adherence improved over the intervention period (Arrivillaga et al, 2014); the other found entrepreneurial training was independently associated with lower LTFU and reduced mortality among adult PLHIV in Uganda (Talisuna-Alamo et al, 2012). Similarly, participants in an intervention in Ethiopia which included entrepreneurial training and other HES support, reported better adherence than a comparison group (Bezabih, 2016).…”
Section: Mediummentioning
confidence: 99%
“…Although medical record data captured important sociodemographic factors associated with group microfinance participation (e.g. wealth proxies, household conditions), it is still possible that imbalances exist between the comparison groups in terms of unmeasured covariates, such as treatment adherence [10,12], group cohesion [12,41], or spousal support [12,41]. If these unmeasured covariates are confounders, then the matching methods could potentially exacerbate bias in treatment effect estimates.…”
Section: Discussionmentioning
confidence: 99%